To help others or not: A moderated mediation model of emotional dissonance - Hu, Ling; Huang, Stanley Y. B.; Li, Hung-Xin; Lee, Shih-Chin (Frontiers in Human Neuroscience, 2022)
This article proposes a moderated mediation model of emotional dissonance. In the model, emotional leadership negatively affects emotional dissonance, which, in turn, negatively affects helping behavior. Furthermore, the negative effect of emotional dissonance is assumed to be moderated by work-family conflict. Direct effects from both emotional leadership and work-family conflict to helping other behavior are also considered. Previous studies have neglected the mechanism of emotional dissonance, but this paper fills the gap with a moderated mediation model of emotional dissonance. This article not only provides an incremental contribution to the emotional dissonance literature but also suggests means by which companies might enhance employe helping behaviors in order to achieve greater organizational efficiency.